(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2025)
A comprehensive assessment of butterfly diversity requires effective sampling techniques tailored to species behavior and habitat conditions. This study evaluates butterfly populations and their distribution in two deciduous moist Sal forests of Bangladesh—Bhawal and Madhupur—dominated by the tree Shorea robusta. As part of a broader conservation initiative, we conducted year-round surveys using four sampling techniques: sweep netting, visual observation, fruit-feeding, and sap-feeding. Sampling was performed twice monthly at ten sites (five per forest) between 7:30 a.m. and 6:00 p.m. Visual observation recorded the highest mean butterfly abundance (158.38±29.51), while sap-feeding yielded the lowest (0.23±0.23). Variability was highest for sap-feeding (coefficient of variance: 781.02) and lowest for sweep netting (136.53). Sweep netting effectively captured fast-flying species, visual observation facilitated non-invasive identification, and fruit- and sap-feeding targeted specific butterfly guilds, enhancing species inventory completeness. Our findings highlight the importance of integrating multiple techniques to reduce species-specific biases and ensure robust biodiversity assessments in tropical forests. J. biodivers. conserv. bioresour. manag. 10(2), 2024: 1-14